Estimating locus heterogeneity in autosomal dominant polycystic kidney disease (ADPKD) in the Spanish population. Issue 11 (November 1993) - Peral, B; San Millán, J L; Hernández, C; Valero, A; Lathrop, G M; Beckmann, J S; Moreno, F
Abstract : Although most mutations causing ADPKD in European populations have been mapped to the PKD1 locus on chromosome 16, some of them appear to be unlinked to this locus. To evaluate the incidence of unlinked mutations in Spain we have typed 31 Spanish families from different geographical sites for six closely linked DNA polymorphic marker loci flanking PKD1 detected by probes D16S85, D16S21, D16S259, D16S125, D16S246, and D16S80. Multilocus linkage analysis indicated that in 26 families the disease resulted from PKD1 mutations, whereas in three families it resulted from mutations in a locus other than PKD1. The two other families were not informative. Using the HOMOG test, the incidence of the PKD1 linked mutations in Spain is 85%. Multipoint linkage analysis in the 26 PKD1 families showed that the disease locus lies in the interval between D16S259(pGGG1) and D16S125(26.6).